Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 6 - Factoring, Solving Equations, and Problem Solving - Chapter 6 Review Problem Set - Page 274: 40



Work Step by Step

Since $(x+2)$ is common to both the terms of the equation, we take it out as a common factor: $3(x+2)-x(x+2)=0$ $(x+2)(3-x)=0$ Now, we equate all the factors to zero to solve the equation: $(x+2)(3-x)=0$ $x+2=0$ or $3-x=0$ $x=-2$ or $x=3$ Therefore, the solution set is {$-2,3$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.